THE IMPORTANCE OF HIGH-RESOLUTION COMPUTED TOMOGRAPHY IN EVALUATING THE EFFICACY OF RITUXIMAB IN PATIENTS WITH INTERSTITIAL LUNG DISEASE IN SYSTEMIC SCLEROSIS - O. A. Koneva; O. V. Desinova; L. P. Ananyeva; N. V. Kovaleva (Научно-практическая ревматология, 2018)
Multi-slice spiral computed tomography (MSCT) of the chest is the gold standard for confirming interstitial changes in the lung; but the role of this technique in evaluating the efficiency of therapy for systemic sclerosis (SSc) has not been fully defined.Objective: to assess the time course of changes in the lung according to chest MSCT findings and pulmonary function test (PFT) results in SSc patients and interstitial lung disease (ILD) during of active treatment.Subjects and methods. The investigation enrolled 42 patients with a reliable diagnosis of SSc who had signs of ILD, confirmed by chest MSCT. The patients’ mean age was 48±2 years; the male-to-female ratio was 1:6; that of diffuse-to-localized SSc patients was 1.5:1 (25 and 17); the mean duration of SSc was 6.6±5.9 years. Over time during therapy, forced lung capacity (FVC) and lung diffusing capacity (LDC) were studied and chest MSCT was performed in all the patients at the time of inclusion in the study and after an average of 29±15.3 months (9 to 70 months). A 10% or more change in PFT results was considered to be of clinical significance. During the follow-up period, the patients were treated with rituximab (RTM) at a mean total dose of 2.5±1.3 g (500 mg to 5 g) in combination with glucocorticoids at a mean dose of 11.7±3.9 mg calculated with reference to prednisolone; 10 (24%) patients also received immunosuppressants.Chest MSCT data were analyzed at 5 levels. The magnitude of changes following the pattern seen in frosted glass, honeycomb, and reticular alterations was estimated using a 4-point (0–3 points) scale at each level. The time course of changes in these parameters and PFT results was separately assessed in patients with less and more than 20% of lung tissue injury in Group A (n=13 (31%) and in Group B (n=29 (69%).Results and discussion. Semiquantitative assessment of changes as evidenced by chest MSCT in SSc patients with ILD did not reveal any changes in their total scores. According to a radiologist’s subjective assessment, there were positive and negative MSCT changes in 8 (19%) and 11 (26%) patients, respectively; the changes were present in 23 (55%) patients. A 10% and more increase in FVC was observed in 16 (38%) patients; its decrease was seen in 3 (7%). Positive and negative LDC changes were found in 5 (12%) and 1 (2.4%) patients, respectively. On average, the group showed a significant FVC increase from 73.2±18.8 to 82±21.8% (p=0.000031) and LDC stabilization. None of the patients with positive MSCT changes exhibited FVC deterioration. During therapy, Groups A and B had positive MSCT changes in 5 (38%) and 3 (10%) cases, respectively (p=0.08); no negative changes were noted in Group A while Group B had negative changes in 11 (38%) cases. FVC increased clinically significantly in 6 (46%) patients in Group A and in 10 (34%) in Group B; this decreased in 1 (8%) and 2 (7%) patients, respectively. FVC was significantly higher in Group A than that in Group B both at the time of study inclusion (88.8±18.6 and 65.4±14.5%, respectively; p=0.0002) and in the long-term period (103.3±15.9 and 74.1±18.5%; p=0.0009), while during therapy this increased statistically significantly in both groups (p=0.016 and p=0.0014, respectively). In Groups A and B, the median FVC increments were 10.2 (4.7; 21.9)% and 5.9 (2.75; 14.7)% , respectively (p>0.05). The mean frosted glass score was significantly lower in Group A than that in Group B both at the time of study inclusion (2.9±2.3 and 6.6±2.7; p=0.01) and in the long-term period (1.6±1.4 and 6.4±3.0, respectively; p=0.000006) and this tended to decrease during therapy. A similar pattern was observed with reticular alterations(4.3±2.7 and 8.7±3.2 (p=0.001) and 3.1±2.5 and 8.8±2.0 (p<0.00001), respectively). In Group B, honeycomb scores significantly increased (p=0.047).Conclusion. Semiquantitative assessment of structural changes by chest MSCT in SSc patients and ILD did not reveal any changes in their total scores for a sufficiently long follow-up period. At the same time, the frosted glass scores significantly decreased in patients with an ILD area of <20%, and the honeycomb scores significantly increased in those with >20% of lung tissue injury. During active therapy, the entire group displayed an increase in FVC, as well as LDC stabilization, and their median increments were higher in the patients with an ILD area of <20%. These findings allow the baseline pulmonary injury area to be considered as a potential predictor for a response to therapy in SSc patients with ILD.